A method of reverse and revision of material mechanics performance parameters for vehicle collision simulation. (June 2021) - Wang, Feng; Yan, Haohao; Zhou, Quan; Zhao, Shijin; Xu, Xiaowei
Abstract: In the process of vehicle collision, the steel material will be deformed by the impact speed. The stress under the same strain will be affected by the change of strain rate. The accuracy of the strain rate curve directly determines the accuracy of the model simulation. This article studies the optimization of material mechanical performance parameters and the correction reprocessing methods of the stress that cannot be obtained by the test in the strain interval. This paper proposes the principle of the modified constitutive equations and the corresponding formula. Based on the approximate model of thin-walled beam under the dynamic impact, the correction coefficient is obtained reversely. While ensuring the accuracy between fitting curve based on the material constitutive equation and the experimental data, the modified constitutive model solves the effect of the non-convergence of stress in a large strain region on the accuracy of the collision simulation model. The dynamic drop weight test results of thin-walled beams show that the modified constitutive equation has great significance for improving the accuracy of simulation models under high-speed impact conditions. Highlights: The fitting error has an increasing trend at large strain. The corresponding formula of constitutive equation can improve prediction accuracy. The correction coefficient k can be obtained inversely through the dynamic impact model of thin-walled beam.